The relationship between the determinants of rental housing satisfaction and considering moving in Finland. Issue 2 (14th April 2014) - M. Gibler, Karen; Tyvimaa, Tanja; Kananen, Juha
Abstract : Purpose: – The purpose of this paper is to discuss the relation between dissatisfaction with housing conditions and considering moving among residents of Finnish rental multifamily buildings. The paper examines physical attributes, socioeconomic factors, and subjective opinions related to housing conditions and satisfaction with housing. Design/methodology/approach: – Logistic regression analysis is used to examine survey data to analyse which factors contribute to dissatisfaction with the housing unit and the apartment building and whether dissatisfaction is related to consideration of moving. Findings: – The findings indicate that dissatisfaction with the building and individual housing unit are associated with greater probability of considering moving. Satisfaction with kitchen, living room, storage, and building age are the most important indicators of satisfaction with the housing unit, and satisfaction with living room, bathroom, storage, and building age are associated with satisfaction with the apartment building. These are the areas in which landlords could invest in renovations to increase satisfaction in an attempt to reduce turnover. Research limitations/implications: – The study is conducted with Finnish data only. The sample is not a representative sample of the Finnish population. A longitudinal study would be needed to determine whether dissatisfied residents indending to move actually change residence. Originality/value: – This study is the first of its kind in the Finnish housing market. It tests a general model that has been suggested to be customized to local conditions. In addition, much of the research on this topic is more than 20 years old. Examination of the model under current housing and socioeconomic conditions is necessary to determine if relationships have changed over time.